Energy efficient thermal comfort predictive control for household heat metering room - Xucheng Chang; Bing Kong (Energy Reports, 2022)
Heating accounts for about a quarter of the building’s energy consumption. In order to increase the value of green buildings, it is necessary to do some research on reducing heating energy consumption. The use of household heat metering in buildings can reduce the energy required for heating. In view of the regulation and control problems in energy consumption reduction and thermal comfort improvement, an energy efficient thermal comfort model predictive control (EETCMPC) method was proposed in the household thermal metering building. Firstly, the dynamic temperature change model of the heating room was analyzed and modeled. Then, the structure of EETCMPC system for household thermal metering room was presented, and the thermal comfort index based on Predicted Mean Vote (PMV) was introduced into the cost function, and the EETCMPC was designed. Finally, the performance of EETCMPC was analyzed and verified by means of simulation with Proportion Integration Differentiation (PID) and temperature reference tracking MPC (TRTMPC). Energy consumption of EETCMPC was reduced by approximately 4.4% compared with TRTMPC when the thermal comfort demand was met. Therefore, this method is valid and reliable for energy efficient thermal comfort control for household heat metering room and is significant for engineering application.